Stress signalling dynamics of the mitochondrial electron transport chain and oxidative phosphorylation system in higher plants - Dourmap, Corentin (Ann Bot, 2020)
BACKGROUND: Mitochondria play a diversity of physiological and metabolic roles under conditions of abiotic or biotic stress. They may be directly subjected to physico-chemical constraints, and they are also involved in integrative responses to environmental stresses through their central position in cell nutrition, respiration, energy balance and biosyntheses. In plant cells, mitochondria present various biochemical peculiarities, such as cyanide-insensitive alternative respiration, and, besides integration with ubiquitous eukaryotic compartments, their functioning must be coupled with plastid functioning. Moreover, given the sessile lifestyle of plants, their relative lack of protective barriers and present threats of climate change, the plant cell is an attractive model to understand the mechanisms of stress/organelle/cell integration in the context of environmental stress responses. SCOPE: The involvement of mitochondria in this integration entails a complex network of signalling, which has not been fully elucidated, because of the great diversity of mitochondrial constituents (metabolites, reactive molecular species and structural and regulatory biomolecules) that are linked to stress signalling pathways. The present review analyses the complexity of stress signalling connexions that are related to the mitochondrial electron transport chain and oxidative phosphorylation system, and how they can be involved in stress perception and transduction, signal amplification or cell stress response modulation. CONCLUSIONS: Plant mitochondria are endowed with a diversity of multi-directional hubs of stress signalling that lead to regulatory loops and regulatory rheostats, whose functioning can amplify and diversify some signals or, conversely, dampen and reduce other signals. Involvement in a wide range of abiotic and biotic responses also implies that mitochondrial stress signalling could result in synergistic or conflicting outcomes during acclimation to multiple and complex stresses, such as those arising from climate change.